Последние адреса: мемориальные доски как место памяти и форма коммуникации - Khrushcheva, Daria (Studia Rossica Posnaniensia, 2024)
Memorial plaques are one of the most common forms of commemorative practices. Organically fitting into the geographical and socio-cultural landscape and having several functions, memorial plaques not only become a kind of marker of a “site of memory” (lieu de mémoire), play an important role in preserving names, transmitting historical memory, but also contribute to the construction and consolidation in the mass consciousness of ideologically verified representations of historical political events. Various “initiatives from below” and projects of independent activists (for example, the “Last Address” (“Poslednij adres”) project with memorial tablets to victims of state terror or the anonymous “questions about repressions” action discussed in this article) become vivid examples of how today’s Russian civil society reacts to a unilateral submission historical facts by power structures. The organizers of such actions become new actors in the politics of memory. They seek not only to expand the space of specific “places of memory” – memorial plaques and their contents – but also to change the perception of certain historical events and attitudes towards them. On the example of memorial plaques as a form of commemoration, the article examines the communicative strategies of different groups of memory subjects in modern Russia.